Dynamic tumor-tracking radiotherapy with real-time monitoring for liver tumors using a gimbal mounted linac. Issue 3 (December 2015) - Iizuka, Yusuke; Matsuo, Yukinori; Ishihara, Yoshitomo; Akimoto, Mami; Tanabe, Hiroaki; Takayama, Kenji; Ueki, Nami; Yokota, Kenji; Mizowaki, Takashi; Kokubo, Masaki; Hiraoka, Masahiro
Abstract: Purpose: Dynamic tumor-tracking stereotactic body radiotherapy (DTT-SBRT) for liver tumors with real-time monitoring was carried out using a gimbal-mounted linear accelerator and the efficacy of the system was determined. In addition, four-dimensional (4D) dose distribution, tumor-tracking accuracy, and tumor-marker positional variations were evaluated. Materials and methods: A fiducial marker was implanted near the tumor prior to treatment planning. The prescription dose at the isocenter was 48–60 Gy, delivered in four or eight fractions. The 4D dose distributions were calculated with a Monte Carlo method and compared to the static SBRT plan. The intrafractional errors between the predicted target positions and the actual target positions were calculated. Results: Eleven lesions from ten patients were treated successfully. DTT-SBRT allowed an average 16% reduction in the mean liver dose compared to static SBRT, without altering the target dose. The average 95th percentiles of the intrafractional prediction errors were 1.1, 2.3, and 1.7 mm in the left–right, cranio-caudal, and anterior–posterior directions, respectively. After a median follow-up of 11 months, the local control rate was 90%. Conclusions: Our early experience demonstrated the dose reductions in normal tissues and high accuracy in tumor tracking, with good local control using DTT-SBRT with real-time monitoring in the treatment of liver tumors.